2017
DOI: 10.3168/jds.2016-12105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precalving body condition and prepartum feeding level on gene expression in circulating neutrophils

Abstract: Extensive metabolic, physiological, and immunological changes are associated with calving and the onset of lactation. As a result, cows transitioning between pregnancy and lactation are at a greater risk of metabolic and infectious diseases. The ability of neutrophils to mount an effective immune response to an infection is critical for its resolution, and increasing evidence indicates that precalving nutrition affects postpartum neutrophil function. The objectives of the current study were to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Contreras et al (2004) demonstrated that cows with BCS ≤3 at dry off gained BCS during the dry period and were less likely to have retained fetal membranes compared with cows with BCS ≥3.25 at dry off. Cows managed from late gestation to 21 d before the expected calving date to be thinner (2.75 vs. 3.25) had neutrophils with reduced inflammatory state and an enhanced capacity for microbial destruction (Crookenden et al, 2017). Kadivar et al (2014) suggested, however, that reduced BCS 2 wk prepartum was associated with increased incidence of clinical endometritis, but change in BCS from 2 wk prepartum to 2 or 4 wk postpartum was not associated with clinical endometritis.…”
Section: Introductionmentioning
confidence: 99%
“…Contreras et al (2004) demonstrated that cows with BCS ≤3 at dry off gained BCS during the dry period and were less likely to have retained fetal membranes compared with cows with BCS ≥3.25 at dry off. Cows managed from late gestation to 21 d before the expected calving date to be thinner (2.75 vs. 3.25) had neutrophils with reduced inflammatory state and an enhanced capacity for microbial destruction (Crookenden et al, 2017). Kadivar et al (2014) suggested, however, that reduced BCS 2 wk prepartum was associated with increased incidence of clinical endometritis, but change in BCS from 2 wk prepartum to 2 or 4 wk postpartum was not associated with clinical endometritis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our findings and those ones described by Chebel et al (2018), it seems that monitoring BCS throughout lactation with the goal of achieving moderate BCS at dry-off may be beneficial for transition health. This strategy has been tested in grazing cows by comparing cows that had their BCS experimentally manipulated to achieve moderate BCS at dry-off to cows that had slightly higher BCS at dry-off; the animals with lower BCS had better metabolic (Roche et al, 2015) and immune status (Crookenden et al, 2017) during the transition period.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the over-mobilization of body stores during the period of NEB ( Negative Energy Balance) is a key factor for disease susceptibility in modern dairy cattle ( Crowe et al, 2018). Researchers have reported that the immune system of cows under metabolic stress is further reduced, demonstrating a relationship between metabolic status and peripartum immune function (Crookenden et al, 2017).…”
Section: Nutritional Management Of Transition Cowsmentioning
confidence: 99%